Representation of Student Mental Health in Online Media: Linguistic Corpus Analysis Based on Framing and Critical Discourse - Fitri Farihatul Janah; Widodo, Pratomo (Jurnal Riset Komunikasi (JURKOM), 2026)
The issue of student mental health has received increasing attention in online media coverage as academic pressure and institutional demands in higher education have increased. This study aims to analyze how student mental health is represented in the online media Kumparan through a corpus linguistic approach combined with framing theory (Entman, 1993), Fairclough’s (1995; Critical Discourse Analysis 2010), and the corpus linguistic methodological perspectives of Baker (2006) and McEnery & Hardie (2012). The research data consisted of 30 news articles published between 2021 and 2025 and analyzed using AntConc software through word frequency, collocation, and keyword in context (KWIC) techniques. The results showed that students were represented as a vulnerable group experiencing academic pressure, while campuses were ambiguously positioned as both a source of pressure and a provider of psychological support. The main findings explicitly confirm that the media predominantly frames the issue of student mental health in an individualistic manner rather than as a structural or institutional problem. This study reinforces corpus-based media framing studies in the context of the discourse on student mental health in Indonesia.